Differences in Ankle Neuromuscular Control Between the Preferred Speed and Fixed Speeds During Walking - Ting Yu; Shaofeng Zhao; Yueling Lyu; Xianyi Zhang (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Walking at the preferred speed, considered as a self-optimized gait pattern, is associated with improved energy conservation and cognitive abilities. However, the neuromuscular mechanisms underlying the benefits of the preferred walking speed remain unclear. Therefore, this study aimed to determine the differences in ankle neuromuscular control between the preferred and fixed speeds during walking. Eighteen healthy young adults were recruited to perform overground barefoot walking at the preferred speed, the prefer-matched control speed (PMCS), slower fixed speeds (1, 2, 3 and 4 km/h) and faster fixed speeds (5 and 6 km/h). Muscle synergies and intermuscular coherence were calculated using surface electromyography (EMG) signals of ankle muscles. Results showed that the preferred walking speed exhibited one less muscle synergy and higher intermuscular coherence in 8-42 Hz than the PMCS. Additionally, slow walking speeds performed more muscle synergies and weaker couplings between plantar flexors in 26-60 Hz than the preferred speed and faster fixed speeds. Our results demonstrate an impact of the preferred walking speed on ankle neuromuscular control during walking, which might influence energy consumption and brain resource occupation. Besides, the preferred walking speed and faster fixed speeds showed comparable modular control characteristics of ankle muscles, which might provide suggestions for experimental settings when examining individuals’ natural neuromuscular control features.